Case reportCervical brachytherapy technique for locally advanced carcinoma of the cervix in a patient with septate uterus - Platta, Christopher S.; Wallace, Charlie; Gondi, Vinai; Das, Rupak; Straub, Margaret; Al-Niaimi, Ahmed; Applegate, Glenn; Bradley, Kristin A. (Journal of Contemporary Brachytherapy, 2014)
Purpose : To describe an approach to cervical brachytherapy in a patient with congenital septate uterus and locally advanced cervical carcinoma. Material and methods: The patient is a 34-year-old female with septate uterus presenting with pelvic pain. Workup demonstrated a stage IIB cervical adenocarcinoma with imaging evidence of an involved right external iliac lymph node. The patient received whole pelvic radiation, with concurrent weekly cisplatin (40 mg/m 2 ), to a dose of 45 Gy in 25 fractions followed by a parametrial boost of 5.4 Gy and an additional nodal boost of 9 Gy. Results: The patient was initiated on cervical brachytherapy following fraction 23 of pelvic radiation. To conform to her septated uterus, a Rotte-Y tandem was used. Additionally, 2 CT-compatible ovoids were placed in the vaginal apex to enhance dose distribution and coverage of the target volume. Each fraction of brachytherapy was performed with CT-based planning. A high-risk clinical target volume (HR-CTV) and normal structures were defined and constrained per American Brachytherapy Society (ABS) and Groupe Européen de Curiethérapie/European Society for Therapeutic Radiology and Oncology (GEC-ESTRO) guidelines. The brachytherapy dose was 27.5 Gy in 5 fractions of 5.5 Gy each, prescribed to the HR-CTV. Conclusions : Herein, we report the first documented case of cervical brachytherapy in a patient with septate uterus and locally advanced cervical carcinoma. Using CT-guided planning, in conjunction with the ABS and GEC-ESTRO guidelines, the patient was effectively treated with adapted cervical brachytherapy, meeting criteria for HR-CTV coverage and normal tissue tolerances.